2005
DOI: 10.1128/iai.73.11.7340-7347.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Priming Improves Clearance ofPseudomonas aeruginosain Wild-Type and Interleukin-10 Knockout Mice

Abstract: Endotoxin (lipopolysaccharide [LPS]) tolerance is an altered state of immunity caused by prior exposure to LPS, in which production of many cytokines, including gamma interferon (IFN-␥) and interleukin-12 (IL-12), are reduced but secretion of the anti-inflammatory cytokine IL-10 is increased in response to a subsequent LPS challenge. This pattern of cytokine production is also characteristic of postinflammatory immunosuppression. Therefore, we hypothesized that LPS-primed mice would exhibit an impaired ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 40 publications
5
38
0
1
Order By: Relevance
“…Furthermore, the expression of TNF-␣ and IL-6 is differentially regulated in response to P. aeruginosa (34). We also found that pretreatment with LPS reduced the loads of P. aeruginosa in tissues in both wild-type and RICK-deficient mice, which is consistent with a previous study (38). In addition, this effect of LPS is similar to that observed when mice are pretreated with lipopeptide which resulted in increased bacterial clearance after infection with Salmonella (32).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the expression of TNF-␣ and IL-6 is differentially regulated in response to P. aeruginosa (34). We also found that pretreatment with LPS reduced the loads of P. aeruginosa in tissues in both wild-type and RICK-deficient mice, which is consistent with a previous study (38). In addition, this effect of LPS is similar to that observed when mice are pretreated with lipopeptide which resulted in increased bacterial clearance after infection with Salmonella (32).…”
Section: Discussionsupporting
confidence: 81%
“…During infection with gram-negative organisms, LPS and other bacterial molecules are released into the blood circulation system, and systemic exposure to these stimuli is known to be harmful to the host (8,9,21). Stimulation of host cells with LPS is known to induce the production of proinflammatory cytokines through the activation of Toll-like receptor 4 (TLR4) and to affect host survival and immune responses to invading gram-negative bacteria (30,38). However, the interplay between TLR4 and other innate signaling pathways in the regulation of proinflammatory responses and host survival after gram-negative infection remains poorly understood.…”
mentioning
confidence: 99%
“…The increased IL-10 expression after Tim-3 blockade in vivo might explain the nonsignificant upregulation of TNF-a in vivo, as IL-10 is known to downregulate TNF-a expression (53). IL-10 is known to be an anti-inflammatory cytokine, but has also been linked to impaired bacterial clearance in sepsis (54), and elevated IL-10 expression in critically ill patients has been correlated with a poor outcome from sepsis (55). Thus, blockade of Tim-3 upregulation of IL-10 expression may not be beneficial but, rather, detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ligand-induced tolerance may represent a negative feedback mechanism invoked to induce inflammation resolution and restore homeostasis after TLR activation (28). Preconditioning of animals to TLR ligands such as lipopolysaccharide (LPS) (32,50,56), bacterial lipoproteins (7,16,34), and flagellin (27,28,58) has been shown to provide protection against infection and sepsis in animal models. The retina is extremely sensitive to inflammation-mediated damage (60).…”
mentioning
confidence: 99%